We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
33
7
avatar+15 

Find the solution of the equation ln24x-1 = ln8x+5+ log2161-2x expressing your answer in terms of ln2. 

 Dec 3, 2019
 #1
avatar
+1

\(ln2^{4x-1}=ln8^{x+5}+log_2 16^{1-2x}\)

the right handside \(log_2 16^{1-2x}\) we can make the power (1-2x) next to the log so we could solve for 2^y=16 which will be 4 

\((1-2x)*log_2 16\)

\(log_2 16 = 4\)

4*(1-2x) + \(ln8^{x+5}\)=\(ln2^{4x-1}\)

4-8x+(x+5)*\(ln8\)=(4x-1)*\(ln2\)

\(\frac{4-8x+(x+5)*ln8}{4x-1}=ln2\)

Expressed in terms of ln2 

Further simplify could be done by using calculator 

ln8=2.07944154

4-8x+(x+5)*2.07944154

4-8x+2.079444154x+10.3972077

4-5.920x+10.3972077 

14.3972077-5.920x/4x-1 =ln2 

ln2=0.693147

14.4-5.9x=(4x-1)*0.693147

Rest is just algebra and indeed you will find that 

indeed you will find x=1.73589087 approx: 1.74 

Which works.

I don't think the question wants the x value so just expressed it in ln2 

 Dec 3, 2019
edited by Guest  Dec 3, 2019
 #2
avatar
0

I.E a much faster way was just (4x-1)*ln2=\(ln8^{x+5}+log_2 16^{1-2x}\)

Divide by (4x-1) 

\(ln2\) = \(\frac{ln8^{x+5}+log_2 16^{1-2x}}{4x-1}\)

Guest Dec 3, 2019
 #3
avatar+15 
0

the answer key says that it should be x=(16ln2+4)/(ln2+8) 

i just dont know how to get there

 Dec 3, 2019
 #4
avatar
0

But the model answer solved for x, While the question asked for an expression in terms of ln2 

Guest Dec 3, 2019
 #5
avatar+15 
0

i think it means solve for x and show what x is in terms of ln2

cherrypiedelicious  Dec 3, 2019
 #6
avatar
0

ohh! sorry! 

I gtg now, i am pretty sure someone will help you soon! (If not i will do later) 

Guest Dec 3, 2019
 #7
avatar+105989 
+1

Find the solution of the equation .... expressing your answer in terms of ln2. 

 

\(ln2^{4x-1} = ln8^{x+5}+ log_216^{1-2x}\\ \text{I will assume that you mean}\\ ln(2^{4x-1}) = ln(8^{x+5})+ log_2(16^{1-2x})\\ (4x-1)ln(2) =(x+5) ln(8)+ (1-2x)log_2(16)\\ (4x-1)ln(2) =(x+5) ln(2^3)+ (1-2x)log_2(2^4)\\ (4x-1)ln(2) =3(x+5) ln(2)+4 (1-2x)log_2(2)\\ (4x-1)ln(2) =3(x+5) ln(2)+4 (1-2x)\\ [(4x-1)-3(x+5)]ln2=4(1-2x)\\ [4x-1-3x-15)]ln2=4(1-2x)\\ [x-16)]ln2=4(1-2x)\\ xln2-16ln2=4-8x\\ xln2+8x=4+16ln2\\ x(ln2+8)=\\ x=\frac{4(1+4ln2)}{ln2+8}\\ x=\frac{16ln2+4}{ln2+8}\) 

 

 

 

 

--------------------------------------------------------

Coding:

 

ln2^{4x-1} = ln8^{x+5}+ log_216^{1-2x}\\
\text{I will assume that you mean}\\
ln(2^{4x-1}) = ln(8^{x+5})+ log_2(16^{1-2x})\\
(4x-1)ln(2) =(x+5) ln(8)+ (1-2x)log_2(16)\\
(4x-1)ln(2) =(x+5) ln(2^3)+ (1-2x)log_2(2^4)\\
(4x-1)ln(2) =3(x+5) ln(2)+4 (1-2x)log_2(2)\\
(4x-1)ln(2) =3(x+5) ln(2)+4 (1-2x)\\
[(4x-1)-3(x+5)]ln2=4(1-2x)\\
[4x-1-3x-15)]ln2=4(1-2x)\\
[x-16)]ln2=4(1-2x)\\
xln2-16ln2=4-8x\\
xln2+8x=4+16ln2\\
x(ln2+8)=\\
x=\frac{4(1+4ln2)}{ln2+8}\\
x=\frac{16ln2+4}{ln2+8}

 Dec 3, 2019

19 Online Users

avatar
avatar